DEVELOPMENT OF SCIENCE LITERACY ASSESSMENT INSTRUMENTS IN SCIENCE LEARNING USING CONTEXTUAL LEARNING MODELS FOR JUNIOR HIGH SCHOOL - Eka Fitria Nur Islamiyah; Binar Ayu Dewanti; Agus Santoso (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
In order to address the lack of reliable scientific literacy assessment tools in many schools, it became necessary to develop new instruments. Unfortunately, most teachers had not previously conducted comprehensive scientific literacy assessments or used assessment tools that followed independent curriculum assessment guidelines. As a result, this study was undertaken to create a valid and reliable scientific literacy assessment tool for junior high school students. The assessment tool utilized five scientific literacy indicators: understanding phenomena, explaining phenomena scientifically, using scientific evidence, solving problems, and identifying scientific problems in the earth and solar system. The 4D research and development method was employed in this study, with the development stages simplified to 3D. Research instruments included validation sheets and scientific literacy tests. The final product is a scientific literacy assessment tool consisting of 16 essay questions. Results from content/expert validity testing by material and language experts were 0.83%, and the empirical validation results of the 16 essay questions as a whole were deemed valid. Additionally, reliability testing yielded a value of 0.960, indicating very high reliability. Testing the hypothesis on the left side showed that at least 61% of students possessed scientific literacy abilities, with the same proportion found to be at the developing and advanced stages. However, 11% of students were still in the beginning stages, indicating that they had not yet met the learning objectives criteria.